Educating the Next Generation MSc in Cyber Security - Carlsson, A.; Sokolianska, I.; Adamov, A. (My University, 2019)
The degree project is conducted at the end of the education programs that lead to Bachelor’s, Master’s, and Master of Science in Engineering (MSE) degrees. The purpose of the project for a student is to practice the necessary skills used to independently define,plan, conduct, and present a project. The projects focus on research, on development,or contain a blend of both.
Keywords: advanced network; cloud security; wirelles; web security